On evaporation smoothing mechanism of metal surface under the irradiation by submicrosecond ion beams; 9th International Conference on Modification of Materials with Particle Beams and Plasma Flows, Tomsk, 21-21September 2008 - Bleykher (Bleicher) G. A. Galina Alekseevna
Lately it has been revealed that pulsed charged particle beams are able to diminish the micropeaks on the irradiated surface and in that way to decrease its roughness. But it isn't clear now what mechanisms produce this effect. Most likely the superposition of various mechanisms takes place, at that the contribution of each one is different in dependence on the beam parameters and the target properties. It's been supposed that the preferred evaporation of peaks is able to be one of the dominating mechanism when submicrosecond ion beams with the ion energy of 100...1000 keV and the power density of 10{7}...10{9} W/cm{2} are used. The calculations have been carried out confirmed this supposition. The analysis of micropeak reduction effectiveness depending on beam parameters has been realized.